2004
DOI: 10.1128/jvi.78.20.11321-11326.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a DNA Influenza Virus Vaccine Is Markedly Increased by the Coadministration of a Schiff Base-Forming Drug

Abstract: Effective vaccination against heterologous influenza virus infection remains elusive. Immunization with plasmid DNA (pDNA) expressing conserved genes from influenza virus is a promising approach to achieve cross-variant protection. However, despite having been described for more than a decade, pDNA vaccination still requires further optimization to be applied clinically as a standard vaccination approach. We have recently described a simple and efficient approach to enhance pDNA immunization, based on the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The lack of activity found for uncoordinated ligand 2 and its Cu(II) and Zn(II) complexes is similar to that previously reported [8] 2 ] against the same organisms (except MRSA, which was not tested). In contrast to the relative inactivity of 2, a related Schiff base, formed from Apim and 2-formylphenox yacetic acid, was found to be quite active in its uncoordinated form against strains of S. aureus and E. Coli (MIC 100 value of 6.25 lg/ml in each case), indicating the importance of functionalization of the salicylate phenyl ring [14].…”
Section: Antimicrobial Activitysupporting
confidence: 88%
See 1 more Smart Citation
“…The lack of activity found for uncoordinated ligand 2 and its Cu(II) and Zn(II) complexes is similar to that previously reported [8] 2 ] against the same organisms (except MRSA, which was not tested). In contrast to the relative inactivity of 2, a related Schiff base, formed from Apim and 2-formylphenox yacetic acid, was found to be quite active in its uncoordinated form against strains of S. aureus and E. Coli (MIC 100 value of 6.25 lg/ml in each case), indicating the importance of functionalization of the salicylate phenyl ring [14].…”
Section: Antimicrobial Activitysupporting
confidence: 88%
“…In recent years, metal complexes comprising Schiff base ligands have been shown to exhibit significant anticancer, antiviral and antimicrobial activity [1][2][3][4]. Commercially available 1-(3-aminopropyl)imidazole (Apim) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to humoral immunity, co-administration of oxidized carbohydrates with antigen increases the secretion of antigen-specific immunoglobulins. Parallel studies of T cell-dependent immune responses demonstrate similar increases in responsiveness when using the Schiff base-forming agent tucaresol during immunization [69]. Furthermore, endogenous NO generation by cytokine induction in immune-related cells and exogenous NO (provided locally by NO-releasing compounds) have been demonstrated to be essential for the priming of the immune response (T cell priming) against specific antigens and some tumor associated antigens (TAAs) [57,70].…”
Section: Nitric Oxide Rns Ros and Anti-cancer Therapymentioning
confidence: 88%
“…[4][5][6][7] In this context, with the aim of developing new antifungal and antibacterial compounds, we report the synthesis, characterization of a novel Schiff base and its metal complexes and their antifungal, antibacterial properties. While the antibacterial studies exhibit moderate activity against the species studied, antifungal studies revealed an interesting result.…”
Section: Introductionmentioning
confidence: 99%